Enhanced Synaptic Activity and Epileptiform Events in the Embryonic KCC2 Deficient Hippocampus - Khalilov, Ilgam (Frontiers Research Foundation, 2011)
The neuronal potassium-chloride co-transporter 2 [indicated thereafter as KCC2 (for protein) and Kcc2 (for gene)] is thought to play an important role in the post natal excitatory to inhibitory switch of GABA actions in the rodent hippocampus. Here, by studying hippocampi of wild-type (Kcc2(+/+)) and Kcc2 deficient (Kcc2(−/−)) mouse embryos, we unexpectedly found increased spontaneous neuronal network activity at E18.5, a developmental stage when KCC2 is thought not to be functional in the hippocampus. Embryonic Kcc2(−/−) hippocampi have also an augmented synapse density and a higher frequency of spontaneous glutamatergic and GABA-ergic postsynaptic currents than naïve age matched neurons. However, intracellular chloride concentration ([Cl(−)](i)) and the reversal potential of GABA-mediated currents (E(GABA)) were similar in embryonic Kcc2(+/+) and Kcc2(−/−) CA3 neurons. In addition, KCC2 immunolabeling was cytoplasmic in the majority of neurons suggesting that the molecule is not functional as a plasma membrane chloride co-transporter. Collectively, our results show that already at an embryonic stage, KCC2 controls the formation of synapses and, when deleted, the hippocampus has a higher density of GABA-ergic and glutamatergic synapses and generates spontaneous and evoked epileptiform activities. These results may be explained either by a small population of orchestrating neurons in which KCC2 operates early as a chloride exporter or by transporter independent actions of KCC2 that are instrumental in synapse formation and networks construction.